Organizational Performance and Information Technology Investment Intensity in the Insurance Industry - Harris, Sidney E.; Katz, Joseph L. (Organization Science, 1991)
In this paper, we consider whether there existed a significant and systematic relationship between firm performance and information technology investment intensity in the home office operation of 40 systems technology leaders in the life insurance industry, 1983–1986. It is hypothesized that in top performance insurance firms (1) information technology costs as a proportion of total operating costs were higher, and (2) information technology costs as a proportion of premium income were lower, than in weak performance firms. Evidence is presented that indicates that firm performance was linked to the level of information technology investment intensity.